Cancer mortality in Europe, 1990-92 - F. Levi; F. Lucchini; C. La Vecchia; E. Negri (European Journal of Cancer Prevention, 1995)
Histograms of all age-standardized (world population) death certification rates for 23 cancers or groups of cancers for the period 1990-92 were produced for 35 countries of the European region (including a dozen new national entities) providing data to the World ealth Organization database. Substantial variations were observed in mortality from most common sites. For lung cancer the rate in males was 81/100,000 in Hungary, followed by Belgium, the Czech Republic, the Russian Federation and Poland, while in Sweden, Iceland and Norway, where comprehensive antismoking campaigns have been adopted over the last two decades, the rates were between 24 and 30 per 100,000 males. The lung cancer epidemic in European females is still in its early phases in most countries, with the sole exception of Scotland (29/100,000, ie the highest rates in the world), the rest of the UK, Denmark, Iceland, Ireland and Hungary. With reference to colorectal cancer, the highest rates were in the Czech Republic (38/100,000 males, 21/100,000 females) and other central European countries, and the lowest in Greece, Romania and a few Republics of the former Soviet Union, as well as Finland and Sweden. The highest gastric cancer mortality rates were in the Russian Federation (41/100,000 males, 18/100,000 females), followed by a few Republics of the former Soviet Union and Portugal in Western Europe. The highest breast cancer rates (25-29 per 100,000 females) were in the UK, Belgium, Ireland, The Netherlands, Denmark and other Scandinavian countries. For overall cancer mortality, the range of variation was between 260/100,000 in Hungary and 132/100,000 in Sweden for males, and between 142/100,000 in Denmark and 76/100,000 in Kyrgizstan for females, ie approximately a twofold variation in both sexes.